Moral identity in relation to emotional well-being: a meta-analysis - Goering, Marlon; Espinoza, Carlos N.; Mercier, Alecia; Eason, Emma K.; Johnson, Charles W.; Richter, Caroline G. (Frontiers in Psychology, 2024)
This meta-analytic review surveyed previous empirical studies that examined links between moral identity and indicators of emotional well-being. Additionally, this meta-analysis examined cultural origin as a moderator, testing if links between moral identity and emotional well-being differ in collectivistic vs individualist countries. Drawing on 27 eligible studies, moral identity was associated with greater emotional well-being (r = .27, p <.001). Follow up analyses on individual dimensions showed medium effect sizes in links between moral identity and greater happiness or positive affect (r = .28, p < .001), greater sense of purpose or meaning in life (r = .29, p < .001), and higher self-esteem (r = .25, p < .001). Moreover, moral identity was associated with greater life satisfaction showing a small effect size (r = .15, p = .011). Resultsshowed that effect sizes of links between moral identity and overall emotional well-being did not significantly differ by cultural origin. However, effect sizes tended to be larger in the nine studies that were conducted in collectivistic countries (r = 0.30, p < .001) as compared to the 15 studies that were conducted in individualistic countries (r = 0.27, p < .001). The results of this metaanalysis indicate a robust empirical relationship between moral identity and emotional wellbeing that is present across various dimensions of emotional well-being and in both individualistic and collectivistic cultures.